Research on similarity test design and characteristic verification for tank fires under environmental wind conditions - Yi Jiang; Fang Shen; Zhuo Su; Lijiao Huang (PLoS ONE, 2026)
Petroleum is recognized as a crucial strategic material for national sustainable development, and its safe storage, transportation, and utilization have significant impacts on the human ecological environment. In order to conduct in-depth research on the safety characteristics of oil tank fires, this study primarily employed similarity criteria to design small-scale experiments and further validated the full-scale experiments using numerical simulations. The flame characteristics, thermal physical properties, and “safe distance-time” of large-scale storage tank fires were pointed out. The results showed that with the increase of wind speed, its impact on flame height became smaller and smaller. The suitable wind speed range for the experiment was found to be between 0.97 m/s and 6.64 m/s. The flame surface area and flame volume first decreased and then increased with increasing wind speed, and there was a linear relationship between flame volume and surface area. The flame temperature decreased first and then increased. The larger the flame volume, the higher the heat release rate, and there was a linear relationship between the two. The validation experiment results showed that the temperature error and heat release rate error range of the simulation experiment were less than 5%, indicating a high reliability of the similarity experiments. Additionally, research on the “safe distance-time” relationship of the tank fires indicated that the minimum safe distance for personnel under this engineering condition was 21 m.